The Influence of Content Marketing, Brand Ambassadors and Product Reviews on Purchasing Decisions for Scarlett Whitening Consumers in Pekanbaru City - Putri, Yolanda Harmila; Alvi Furwanti Alwie; Henni Noviasari (West Science Business and Management, 2024)
This study was conducted to determine the effect of content marketing, brand ambassadors, and product reviews on purchasing decisions for Scarlett Whitening consumers in Pekanbaru City. With 190 responders the population in examination was Scarlett Whitening in Pekanbaru City. Purposive and non-probability sampling techniques are used in sample dedicating. Multiple linear regression analysis is the analytical technique utilized in this research, and SPSS V.25 helpline to process the data. Research findings indicate that content marketing has a partial effect on purchasing decisions, brand ambassadors has a partial effect on purchasing decisions, product reviews has a partial effect on purchasing decisions. In addition, there is a simultaneous relationship betweeen content marketing, brand ambassadors, and product reviews and purchasing decisions